The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1177/2325967117740078
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Schöttle Technique in the Pediatric Knee

Abstract: Background:The Schöttle point is commonly used for anatomic femoral tunnel placement during medial patellofemoral ligament (MPFL) reconstruction. This technique has not been previously validated in the skeletally immature patient, in whom femoral tunnel placement may put the distal femoral physis at risk of iatrogenic injury.Hypothesis:Interobserver reliability for femoral tunnel placement will be higher in adult knees compared with pediatric knees.Study Design:Cross-sectional study (diagnosis); Level of evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
(49 reference statements)
0
9
1
Order By: Relevance
“…22,30 The surgical technique for adults and adolescents follows anatomic recommendations for graft placement. 25,31,32 Graft placement on the patella has been consistent, with many groups recommending a broad attachment along the medial border of the patella. 33,34 Avoiding large patellar drill tunnels can reduce the risk of patella fracture.…”
Section: Unique Anatomic Considerations For Mpfl Reconstruction In Sk...mentioning
confidence: 83%
“…22,30 The surgical technique for adults and adolescents follows anatomic recommendations for graft placement. 25,31,32 Graft placement on the patella has been consistent, with many groups recommending a broad attachment along the medial border of the patella. 33,34 Avoiding large patellar drill tunnels can reduce the risk of patella fracture.…”
Section: Unique Anatomic Considerations For Mpfl Reconstruction In Sk...mentioning
confidence: 83%
“…However, graft anchoring in this location may not be appropriate in the skeletally immature patient. 4 Avoiding physeal injury in the pediatric population has been described by identifying the Scho ¨ttle point and then aiming distal to the physis and anterior. 3,8 Some surgeons have alternatively opted to anchor the graft proximal to the physis.…”
Section: Discussionmentioning
confidence: 99%
“…Huston et al 16 evaluated the method of Schӧttle et al 29 in pediatric patients and found it to be reproducible, with a small intraobserver variance. Although reliable in determining the MPFL origin intraoperatively, it is not a reliable method of measurement to determine the distance of the MPFL origin to the physis and should be used with caution in skeletally immature patients.…”
Section: Discussionmentioning
confidence: 99%